2014
DOI: 10.5194/acp-14-8137-2014
|View full text |Cite
|
Sign up to set email alerts
|

Bromocarbons in the tropical coastal and open ocean atmosphere during the 2009 Prime Expedition Scientific Cruise (PESC-09)

Abstract: Abstract. Atmospheric concentrations of very short-lived species (VSLS) bromocarbons, including CHBr 3 , CH 2 Br 2 , CHCl 2 Br, CHClBr 2 , and CH 2 BrCl, were measured in the Strait of Malacca and the South China and Sulu-Sulawesi seas during a two-month research cruise in June-July 2009. The highest bromocarbon concentrations were found in the Strait of Malacca, with smaller enhancements in coastal regions of northern Borneo. CHBr 3 was the most abundant bromocarbon, ranging from 5.2 pmol mol −1 in the Strait… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 30 publications
0
11
1
Order By: Relevance
“…Our simulations in the East China Sea suggest anthropogenic bromoform contributions of 1.7-5.1 ppt near Shanghai, being on the upper side of the observations. Nadzir et al with Nadzir et al (2014). In the Strait of Malacca, our simulations suggest 0.2-0.7 ppt (LOW to MODERATE) which is lower than the observations.…”
Section: Bromoform Measurements In the Marine Boundary Layer 370contrasting
confidence: 64%
“…Our simulations in the East China Sea suggest anthropogenic bromoform contributions of 1.7-5.1 ppt near Shanghai, being on the upper side of the observations. Nadzir et al with Nadzir et al (2014). In the Strait of Malacca, our simulations suggest 0.2-0.7 ppt (LOW to MODERATE) which is lower than the observations.…”
Section: Bromoform Measurements In the Marine Boundary Layer 370contrasting
confidence: 64%
“…The TWP, particularly during boreal winter, is a region of active convection and one of the most important pathways for compounds with short tropospheric lifetimes to reach the stratosphere (Aschmann et al, 2009;Bergman et al, 2012;Levine et al, 2007;Schofield et al, 2011). Consequently, the TWP and nearby Southeast Asia have been regions where a number of ground and ship-based campaigns have been conducted to study oceanic emissions of VSLS (Brinckmann et al, 2012;Mohd Nadzir et al, 2014;Robinson et al, 2014). Additionally, aircraft campaigns observed mixing ratios of VSLS in Southeast Asia that were slightly elevated with respect to measurements collected in the rest of the tropics (Sala et al, 2014;Wisher et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Many terrestrial plants have been identified as sources of CH 3 Cl (Yokouchi et al, 2007), and the results of recent modeling indicate that about 55 % of the global sources of CH 3 Cl originate from tropical lands (Xiao et al, 2010;Carpenter et al, 2014). It has also been suggested that natural terrestrial sources of CH 3 Br, especially emissions from terrestrial vegetation, must account for a large part of the missing sources Yassaa et al, 2009;Warwick et al, 2006;Gan et al, 1998;Yokouchi et al, 2002;Moore, 2006;Rhew et al, 2001;Wishkerman et al, 2008), and emissions have been observed from peatlands, wetlands, salt marshes, shrublands, forests and some cultivated crops (Gan et al, 1998;Varner et al, 1999;Lee-Taylor and Holland, 2000). CHCl 3 has also been found to be emitting from various terrestrial sources, including rice, soil, tundra, forest floor and different types of microorganisms, such as fungi and termites (see Dimmer et al, 2001 andRhew et al, 2008).…”
Section: Introductionmentioning
confidence: 99%